Reconsidering the Age of Marriage in Indonesia - Rajafi, Ahmad (al-'adalah, 2014)
The Government has made the rule about age of marriage, namely the male must be at least 19 years old and the female must be at least 16 years old. Nevertheless, early marriages or under-age mariages are still common in Indonesia since people reffer to the prophet’s Sunnah fi’liyyah who was married to ‘Âisyah. Passion and courage from policy makers to revise the rule of minimum marriage age are required to revise that rule and reviewing the Sunnah is also imperative. It is important because the right of children is a part of human rights that must be guaranteed, protected, and filled by parents, family, society and government.